The “Background Conditions” of the Hedge Fund in General Electric’s Schenectady: Reconsidering the “History of Capitalism” - David Huyssen (Transatlantica)
This article applies Nancy Fraser’s theory of capitalism’s “background conditions” to a grassroots case study: the formative influences of Progressive-Era Schenectady’s social relations on the socialist who created the hedge fund, Alfred Winslow Jones. In showing how “capitalist” background conditions also depended on and cultivated socialist subjectivities that contributed to Jones’s creation of the hedge fund, it illustrates both value and limits in Fraser’s theory and the “history of capitalism” framework.